2018
DOI: 10.1186/s13756-018-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in a tertiary healthcare facility in Ghana: a point prevalence survey

Abstract: BackgroundThe global rise and spread of antibiotic resistance is limiting the usefulness of antibiotics in the prevention and treatment of infectious diseases. The use of antibiotic stewardship programs guided by local data on prescribing practices is a useful strategy to control and reduce antibiotic resistance. Our objective in this study was to determine the prevalence and indications for use of antibiotics at the Korle-Bu Teaching Hospital Accra, Ghana.MethodsAn antibiotic point prevalence survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
100
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(130 citation statements)
references
References 34 publications
27
100
3
Order By: Relevance
“…The prevalence of antibiotic use in the current study was consistent with a similar study conducted in South East Nigeria (78.6%) [10]. The prevalence of antibiotic use among hospitalized patients in Nigeria was higher than other African countries including Ghana (51.4%) [16] and Benin (64.6%) [8], Europe (30.5%) [6], and the United States (49.9%) [7]. The high rate of antibiotic use among hospitalized patients could be attributed to lack of a national antimicrobial guideline to promote rational use of antibiotics in hospital setting.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of antibiotic use in the current study was consistent with a similar study conducted in South East Nigeria (78.6%) [10]. The prevalence of antibiotic use among hospitalized patients in Nigeria was higher than other African countries including Ghana (51.4%) [16] and Benin (64.6%) [8], Europe (30.5%) [6], and the United States (49.9%) [7]. The high rate of antibiotic use among hospitalized patients could be attributed to lack of a national antimicrobial guideline to promote rational use of antibiotics in hospital setting.…”
Section: Discussionsupporting
confidence: 90%
“…The study also found that majority (about 67%) of the patients who used antibiotic on the day of the survey had two or more prescriptions, similar to the result in Ghana [16]. However, the use of multiple antibiotic therapy among hospitalized patients was more than two times higher than Europe's (29.4%) [6].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A proportion of patients higher than recorded in other studies in LMICs [21,22] and high-income countries(HICs) [23] used at least one antibiotic prior to enrollment. The high rate of antibiotic use by this cohort could be a predisposing factor to the high levels of resistance observed in this study, although it could also be explained by the effort of service providers to treat the patients' febrile conditions.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, 77.6% of admitted patients on one single day had consumed at least one antimicrobial. This is much higher than prevalence rates reported in other PPS studies across the world including the Global PPS ( [48]. In Botswana, more than two-thirds of admissions in their PPS study were due to infectious diseases with 40% of those tested were HIV positive [47].…”
Section: Discussionmentioning
confidence: 96%